Transformation of natural relief of a post-mining area – Anthropocene determinant? - Petera-Zganiacz, Joanna; Dzieduszyńska, Danuta (Acta Geographica Lodziensia, 2024)
The strong activation of human pressure on the natural environment dates back to 1950 and this date is often indicated as the beginning of the Anthropocene. In the field of Earth sciences, the Anthropocene is studied in various aspects, including anthropogenic geomorphological changes, which are particularly visible in areas of open-pit mining. Analysis of anthropogeo-morphological forms was carried out in the post-mining area of the Adamów Lignite Mine located in the Warta River valley in the Koło Basin. Forms of the river valley, dunes and peatbogs, as well as small fragments of the plateau were destroyed, and in their place anthropogenic plains, dumping hills and artificial reservoirs were created. The result of such activities is the creation of a new geomorphological landscape as a determinant of the Anthropocene.